Aromatic Profiles and Vineyard Location: Uncovering Malvasija Dubrovačka Wines - Domagoj Ivan Žeravica; Ivana Tomaz; Darko Preiner; Iva Šikuten; Domagoj Stupić; Ana Jeromel; Edi Maletić (Beverages, 2025)
The quality and sensory characteristics of wines are influenced by several factors, including grape variety, local climate, soil conditions, viticultural practices, and vintage. This study investigates the volatile organic compounds (VOCs) in Malvasija Dubrovačka wines, which include various chemical groups such as terpenes, esters, alcohols, acids, and C13-norisoprenoids. The aim was to investigate how vineyard location and vintage influence the VOC profiles of these wines in two consecutive vintages. Using gas chromatography–mass spectrometry, 54 individual VOCs were identified and quantified. The results showed remarkable differences in the composition of VOCs, especially C13-norisoprenoids, terpenes, and acids, between the two vintages and the studied locations. Principal component analysis showed a significant influence of vineyard location on the composition of Malvasija Dubrovačka wines, a result that was reinforced by conventional descriptive analysis (CDA) of sensory testing.